2011
DOI: 10.1371/journal.pone.0016628
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analyses of Cellular Proteins in Methicillin-Resistant Staphylococcus aureus Treated with Rhodomyrtone, a Novel Antibiotic Candidate

Abstract: The ethanolic extract from Rhodomyrtus tomentosa leaf exhibited good antibacterial activities against both methicillin-resistant Staphylococcus aureus (MRSA) and S. aureus ATCC 29213. Its minimal inhibitory concentration (MIC) values ranged from 31.25–62.5 µg/ml, and the minimal bactericidal concentration (MBC) was 250 µg/ml. Rhodomyrtone, an acylphloroglucinol derivative, was 62.5–125 times more potent at inhibiting the bacteria than the ethanolic extract, the MIC and MBC values were 0.5 µg/ml and 2 µg/ml, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 56 publications
7
61
0
Order By: Relevance
“…The extract caused formation of pit, irregular shape, deformed septa, cell wall disintegration, and loss of cytoplasm contents. Similar effects of cell wall had been described for oritavancin, rhodomyrtone and marine bacteria derived antibiotic [18][19][20].…”
Section: Discussionsupporting
confidence: 67%
“…The extract caused formation of pit, irregular shape, deformed septa, cell wall disintegration, and loss of cytoplasm contents. Similar effects of cell wall had been described for oritavancin, rhodomyrtone and marine bacteria derived antibiotic [18][19][20].…”
Section: Discussionsupporting
confidence: 67%
“…Similar cell wall effects have been reported in S. aureus treated with bacteria-derived antibiotics [24,25].…”
Section: Discussionsupporting
confidence: 83%
“…The results indicated that rhodomyrtone inhibited the synthesis of DnaK protein in the treated pathogens (Sianglum et al, 2011). DnaK protein is associated with a wide variety of cellular processes (Hu et al, 2006;Kurt et al, 2006;Singh et al, 2007;Al Refaii & Alix, 2009;René & Alix, 2011), and deletion of dnaK in S. aureus demonstrated an increase in susceptibility to oxidative stress conditions and reduced carotenoid production (Singh et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The MIC and minimum bactericidal concentration values of rhodomyrtone against MRSA range from 0.39 to 0.78 mg ml 21 , which is very close to those of vancomycin (Limsuwan et al, 2009b). Recently, protein profiling of rhodomyrtone-treated MRSA demonstrated alterations in the expression of several major functional classes of bacterial protein (Sianglum et al, 2011;Visutthi et al, 2011). Therefore, the objective of the present study was to investigate inhibition of pigment synthesis in S. aureus after treatment with rhodomyrtone.…”
Section: Introductionmentioning
confidence: 98%